Integrated Conceptual Design of Landing Gear, Propulsion, and Communication Subsystems for a Medium-Altitude Long-Endurance (MALE) Unmanned Aerial Vehicle - Nordin, Nur Asyraf; Omar, Zamri (Progress in Aerospace and Aviation Technology, 2026)
Medium-Altitude Long-Endurance (MALE) unmanned aerial vehicles (UAVs) are widely used for intelligence, surveillance, reconnaissance, and other long-duration missions because of their extended endurance, operational flexibility, and ability to carry mission-specific payloads. The effectiveness of a MALE UAV depends strongly on the integrated configuration of its major subsystems, particularly the landing gear, propulsion, and communication systems. This study presents the conceptual design and integration of these three critical subsystems for a MALE UAV platform benchmarked against operational UAV configurations such as the TAI Anka-S. A retractable tricycle landing gear configuration was selected to provide stable ground handling and improved aerodynamic efficiency when retracted. The propulsion subsystem adopts a rear-mounted pusher configuration powered by a TEI-PD170 turbodiesel engine to support long-endurance operation while maintaining an unobstructed forward payload bay. The communication subsystem combines Line-of-Sight (LOS) and Beyond-Line-of-Sight (BLOS) architecture to support command, control, telemetry, and long-range mission data transmission. Aircraft mass distribution, center of gravity (CG) characteristics, landing gear geometry, and subsystem compatibility were evaluated using conceptual engineering calculations. The results indicate that the proposed configuration provides acceptable mass balance, adequate ground handling characteristics, sufficient propeller ground clearance, and effective subsystem integration. The developed conceptual design provides a technically feasible foundation for subsequent aerodynamic analysis, structural assessment, prototype development, and flight performance evaluation.